Vitamin D and Disease Severity in Multiple Sclerosis—Baseline Data From the Randomized Controlled Trial (EVIDIMS) - Bäcker-Koduah, Priscilla; Bellmann-Strobl, Judith; Scheel, Michael; Wuerfel, Jens; Wernecke, Klaus-Dieter; Dörr, Jan; Brandt, Alexander Ulrich; Paul, Friedemann (Frontiers in Neurology, 2020)
Objective: To investigate the associations between hypovitaminosis D and disease activity in a cohort of relapsing remitting multiple sclerosis (RRMS) and clinically isolated syndrome (CIS) patients. Methods: In 51 RRMS and 2 CIS patients on stable interferon-β-1b (IFN-β-1b) treatment recruited to the EVIDIMS study (Efficacy of Vitamin D Supplementation in Multiple Sclerosis (NCT01440062) baseline serum vitamin D levels were evaluated. Patients were dichotomized based on the definition of vitamin D deficiency reflected by a 25-hydroxyvitamin D (25(OH)D) level <30 ng/ml vs ≥ 30 ng/ml. Possible associations between vitamin D deficiency and both clinical and MRI features of the disease were analyzed. Results: Median (25%, 75% quartiles, Q) 25(OH)D level was 18 ng/ml (12, 24). 48 out of 53 (91%) patients had 25(OH)D levels < 30 ng/ml (p < 0.001). Patients with 25(OH)D ≥ 30 ng/ml had lower median (25%, 75% Q) T2-weighted lesion counts (25 (24, 33)) compared to patients with 25(OH)D < 30 ng/ml (60 (36, 84), p = 0.03; adjusted for age, gender and disease duration: p < 0.001). EDSS score were negatively associated with serum 25(OH)D levels in multiple linear regression, including age, sex and disease duration (adjusted: p < 0.001). Interpretation: Most patients recruited in the EVIDIMS study were vitamin D deficient. Higher 25(OH)D levels were associated with reduced T2 weighted lesion count and lower EDSS scores.